Perilaku Berisiko pada Pengemudi Mobil Berdasarkan Data Demografis - Dian Kemala Putri; Indah Mulyani; Kemal Ade Sekarwati (Universitas Katolik Parahyangan, 2023)
The biggest cause of vehicle accidents is the human factor, one of which is risky driving behaviour. This study aims to provide an overview of the driving behaviour of some drivers and look at the demographic factors (age, gender, driving experience, type of vehicle) behind it. The quantitative approach was used in this study, with descriptive analysis techniques and t-tests on the participant groups. The results of the analysis of 108 drivers as participants in this study indicate that age and gender are factors that can cause car drivers to exhibit risky driving behaviour (speeding, changing lanes, and overtaking vehicles in front). Furthermore, men are more likely to engage in risky driving behaviour, and the older they get, the less likely they are to engage in risky driving behaviour.